ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DENGAN CASH RATIO SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BURSAEFEK INDONESIA - Hotriado Harianja; Ade Fatma Lubis; Zainal Bahri Torong (Program Magister Akuntansi Unsyiah, 2013)
The purpose of this study was 1) to test and analyze the influence of return on asset, return on equity, growth, long term debt, debt equity ratio, debt to total asset, current ratio, profit, earning per share and cash ratio on dividend policy, 2) to test and analyze the factors influencing dividend policy represented by return on asset, return on equity, profit, long term debt, debt to total asset, and current ratio on the consumption goods registered in the Indonesian Stock Exchange, and 3) to test and analyze whether cash ratio as the moderating variable influenced the relationship between return on asset, return on equity, profit, long term debt, debt to total asset, and current ratio and dividend policy. The population of this study was 39 consumption goods companies registered in the Indonesian Stock Exchange from 2008 to 2011, and 12 of them were selected to be the samples for this study through purposive sampling method. The data for this study were obtained from the documentation of financial reports available in the office of Indonesian Stock Exchange. The first hypothesis was procesed through Kaiser-Meyer-Olkin (MKO) method, the second hypothesis was statistically processed through multiple linear regression tests, and the third hypothesis was process through residual test using SPSS program. The result of this study showed that return on asset, return on equity, profit, long term debt, debt to total asset had influence on dividend policy. The result of the second hypothesis test showed that simultaneously return on asset, return on equity, profit, long term debt, debt to total asset had influence on dividend policy and partially only return on equity and current asset had influence on dividend policy. When cash ratio was used as the moderating variable, cash ratio did not strengthen the relationship between the variables of return on asset, return on equity, profit, long term debt, debt to total asset and current ratio and dividend policy. In other words, current ratio is not the moderating variable of dividend policy.Keywords : Return on Asset, Return on Equity, Profit, Long Term Debt, Debt to Total Asset, Current Ratio, Dividend Policy